First-line chemotherapy of advanced or metastatic breast cancer (MBC) with docetaxel and doxorubicin in Indonesia: results from A phase II trial (Medical Journal of Indonesia, 2005)
Doxorubicin and docetaxel as a single agent are known as active cytotoxic agents for the treatment of metastatic breast cancer (MBC). Their combination has also shown to be highly active as a second-line chemotherapy of MBC. This study was design to evaluate the efficacy and safety of docetaxel-doxorubicin combination as first line chemotherapy of MBC patients in Indonesia. Twenty-six female patients between 31-65 years old with advanced or MBC was enrolled. No prior taxane or cumulative doxorubicin of 250 mg/m2 was allowed and patients should not have a heart disease. Treatment consisted of doxorubicin 50 mg/m2 as intravenous (IV) bolus followed one hour later by docetaxel 60 mg/m2 by IV infusion over 1 hour every 3 weeks for 6 cycles. Premedication with oral corticosteroid was administered a day prior to chemotherapy until the second day of each cycle. Left ventricular ejection fraction was recorded at baseline and after the 6th cycle. At the end of study, a total of 156 cycles of chemotherapy have been delivered. Five and 11 patients had a complete response (CR) and partial response (PR), respectively, which accounted for a 61.54% best overall response. Three patients with extensive liver metastases showed complete disappearance after 6 cycles. Most frequent grade 3-4 toxicities were leukopenia (80.77%) and febrile neutropenia (5.77%). Leukopenia was usually short in duration, occurred mainly during the first and second cycle and did not require dose reduction. No patient developed heart failure. There was one death due to progressive disease after 6 cycles. Combination of doxorubicin 50 mg/m2 and docetaxel 60 mg/m2 was sufficiently active as first-line chemotherapy of MBC, especially in patients with liver metastases, with a manageable toxicity profile. (Med J Indones 2005; 14: 20-5) Keywords: docetaxel, doxorubicin, advanced or metastatic breast cancer, phase II trial, anthracycline and taxane combination